Strengthening Students' Religious Character Through Contextual Teaching and Learning in Islamic Elementary Schools - Nurdin, Arbain; Fathiyaturrahmah, Fathiyaturrahmah; Rizqi Syaifulloh, Mohammad (Bahasa Indonesia, Bahasa English, 2025)
This religious character building should ideally begin at an early age, because elementary school is a crucial environment where the foundations of a child's character begin to form. Religious education in elementary school plays a strategic role in strengthening religious character. The contextual learning approach has emerged as a solution, seeking to connect the subject matter with the real lives of students. This study uses a qualitative approach with a case study design. Three main techniques are used: in-depth interviews, participatory observation, and documentation study. Data analysis is conducted using the interactive model of Miles, Huberman, and Saldana, which includes data condensation, data presentation, and conclusions. Meanwhile, data validity techniques include extended observation and triangulation. The results of the study show that the religious education program at SDS Islam Ulul Albab Jember is planned collaboratively with appropriate documents and targets. The program is implemented from morning to noon based on the principles of exemplary behavior and habit formation. Meanwhile, the evaluation process is carried out through tasmi' exams from external parties and monitoring by parents using a book of religious practices. The strengthening of the religious character of students includes a character that not only understands religion in terms of rituals but also its knowledge so that they become closer to Allah. Religious character is strengthened with a variety of contextual strategies through tadarus keliling learning and methods of reprimand and teacher role modeling. Both strategies are part of the Context Teaching and Learning approach, which can have a direct impact on increasing awareness of religion and culture, reminding each other.